1996
DOI: 10.1515/znc-1996-5-624
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Apoptosis in Thymocytes: pH Sensitization

Abstract: Thymocytes were used as a model system to study the effect of microenvironmental pH changes on the radiation-induced apoptosis. We found that the sensitivity of thymocytes toward radiation induced apoptosis is increased by increasing the pH of the incubation me­dium. The major sensitivity change occurs between pH 7 and 8. In a given cell suspension the results obtained where similar when the apoptosis evaluation was carried out either by counting the picnotic nuclei, or monitoring the fraction of apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although an acidic extracellular pH may enhance radiation-induced expression of p53 [83], several studies have shown that low pH ( ∼ 6.5) inhibits or at least delays radiation-induced apoptosis (Table 2) [84][85][86][87][88][89] (also see Fig. 3).…”
Section: Is Radiation-induced Apoptosis Modulated By Ph?mentioning
confidence: 94%
See 1 more Smart Citation
“…Although an acidic extracellular pH may enhance radiation-induced expression of p53 [83], several studies have shown that low pH ( ∼ 6.5) inhibits or at least delays radiation-induced apoptosis (Table 2) [84][85][86][87][88][89] (also see Fig. 3).…”
Section: Is Radiation-induced Apoptosis Modulated By Ph?mentioning
confidence: 94%
“…In one of the aforementioned studies, both an acute (30 min) and a chronic (3 month) exposure to pH 6.8 reduced apoptosis caused by radiation [88]. Radiation-induced apoptosis was enhanced significantly in thymocytes when pH was raised from 7 to 8 [84]. Experiments with murine mammary adenocarcinoma cells indicate a similar response [85].…”
Section: Is Radiation-induced Apoptosis Modulated By Ph?mentioning
confidence: 97%
“…The phase of the cell cycle also affects radiation responses, with cells in G2/M and G1 phases the most radiosensitive and those in the S phase more radioresistant [ 91 , 92 ]. Increased acidification decreases the effectiveness of radiation; cells cultured in acidic media are more resistant to radiation, with acidic pH e shown to reduce fixation of radiation-induced DNA damage, inhibit radiation-induced apoptosis, and delay G2/M-phase arrest allowing more time for treated cells to repair DNA damage, thus increasing radioresistance [ 7 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ].…”
Section: Radiationmentioning
confidence: 99%
“…Indeed, there is evidence that pH may radiosensitize to apoptosis. 51 Previous studies have indicated that low pH can delay radiation-induced apoptosis after low doses (12 Gy and below) due to temporary pH-related cell cycle arrest. 42,43 Other studies using higher doses (20 Gy) 42 demonstrated an inhibition due to cycle delay-independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%